Analysis on the evolution characteristics of kaolin international trade pattern based on complex networks. (August 2022) - Zheng, Shuxian; Zhou, Xuanru; Xing, Wanli; Zhao, Pei
Abstract: This study used a complex network model to analyse the global kaolin trade pattern from 2000 to 2020. The results showed that the kaolin trade between countries tends to be closer, and the trade efficiency keeps improving. The import market tends to be fragmented, which to a certain extent means that the trade voice of kaolin importers is constantly weakening. Compared with import trade, the export trade market has a greater concentration, which is inseparable from resource endowment. Developing countries, such as China and India, have gradually increased their processing capacity of kaolin, and their participation in international kaolin trade has been deepened, which is related to the increase in their industrial production capacity. China and India have gradually increased their control and counter-control over the kaolin trade. But China and India lack a voice in kaolin trade, especially in product pricing. This is because China and India mostly rough-processed kaolin, and most of their kaolin exports are to geo-developing countries. The community evolution of kaolin trade is closely related to the global economy. The kaolin trade exhibits a significant regionalisation trend. With the improvement of the status of the Asian trade community, a systematic and mature kaolin trade market is quietly forming. Finally, this paper puts forward policy suggestions to provide a reference for policymakers to formulate kaolin trade policies. Highlights: Kaolin trade is showing a gradual boom. The trade voice of kaolin importers is constantly weakening. Developing countries gain a foothold in kaolin trade. Developing countries still lack a voice in kaolin trade. The kaolin trade exhibits a regionalisation trend.